The Role of Badan Amil Zakat Nasional (BAZNAS) In Improving Literacy and Community Participation in Fulfilling Agricultural and Livestock Zakat - Sumi; Muhammadun, Muzdalifah; Semaun, Syahriyah (Universitas Muhammadiyah Palu, 2024)
Enrekang Regency is an agrarian region with significant agricultural potential that requires further efforts to improve literacy and community awareness regarding zakat obligations, especially in the context of the agricultural sector. The research method uses qualitative descriptive with data collection techniques through interviews, observations, and documentation. Primary data in this study were obtained from three BAZNAS leaders and 20 farmers and livestock breeders in Enrekang Regency. The obtained data were then analyzed using Nvivo 12 plus software. Secondary data were obtained from the Enrekang Regency Statistics Agency related to the potential agricultural results in Enrekang. The results show that the level of literacy and community participation in fulfilling agricultural and livestock zakat in Enrekang Regency is still low. The community does not yet understand the concept of agricultural and livestock zakat, both in terms of calculation and collection. To improve literacy and community participation in fulfilling agricultural and livestock zakat in Enrekang Regency, BAZNAS has implemented several work programs, including Enrekang Cares, Enrekang Smart, Enrekang Prosperous, Enrekang Healthy, and Enrekang Religious. BAZNAS has also provided assistance to goat breeders, conducted online zakat campaigns, created special videos about agricultural zakat, printed zakat guidebooks in collaboration with educators and communities. However, BAZNAS's efforts to improve literacy and community participation in fulfilling agricultural and livestock zakat in Enrekang Regency have not been effective.